A 3.9 μs Settling-Time Fractional Spread-Spectrum Clock Generator Using a Dual-Charge-Pump Control Technique for Serial-ATA Applications. (12th February 2015) - Kawamoto, Takashi; Suzuki, Masato; Noto, Takayuki
Abstract : A low-jitter fractional spread-spectrum clock generator (SSCG) utilizing a fast-settling dual-charge-pump (CP) technique is developed for serial-advanced technology attachment (SATA) applications. The dual-CP architecture reduces a design area to 60% by shrinking an effective capacitance of a loop filter. Moreover, the settling-time is reduced by 4  μ s to charge a current to the capacitor by only main-CP in initial period in settling-time. The SSCG is fabricated in a 0.13  μ m CMOS and achieves settling time of 3.91  μ s faster than 8.11  μ s of a conventional SSCG. The random jitter and total jitter at 250 cycles at 1.5 GHz are less than 3.2 and 10.7 psrms, respectively. The triangular modulation signal frequency is 31.5 kHz and the modulation deviation is from −5000 ppm to 0 ppm at 1.5 GHz. The EMI reduction is 10.0 dB. The design area and power consumption are 300 × 700  μ m and 18 mW, respectively.